Additive Effects of Mitochondrion-targeted Cytochrome CYP2E1 and Alcohol Toxicity on Cytochrome c Oxidase Function and Stability of Respirosome Complexes - Bansal, Seema (American Society for Biochemistry and Molecular Biology, 2012)
Alcohol treatment induces oxidative stress by a combination of increased production of partially reduced oxygen species and decreased cellular antioxidant pool, including GSH. Recently, we showed that mitochondrion-targeted CYP2E1 augments alcohol-mediated toxicity, causing an increase in reactive oxygen species production and oxidative stress. Here, we show that cytochrome c oxidase (CcO), the terminal oxidase of the mitochondrial respiratory chain, is a critical target of CYP2E1-mediated alcohol toxicity. COS-7 and Hep G2 cell lines expressing predominantly mitochondrion-targeted (Mt(++)) CYP2E1 and livers from alcohol-treated rats showed loss of CcO activity and increased protein carbonylation, which was accompanied by a decline in the steady state levels of subunits I, IVI1, and Vb of the CcO complex. This was also accompanied by reduced mitochondrial DNA content and reduced mitochondrial mRNA. These changes were more prominent in Mt(++) cells in comparison with wild type (WT) CYP2E1-expressing or ER(+) (mostly microsome-targeted) cells. In addition, mitochondrion-specific antioxidants, ubiquinol conjugated to triphenyl phosphonium, triphenylphosphonium conjugated carboxyl proxyl, and the CYP2E1 inhibitor diallyl sulfide prevented the loss of CcO activity and the CcO subunits, most likely through reduced oxidative damage to the enzyme complex. Our results suggest that damage to CcO and dissociation of respirosome complexes are critical factors in alcohol-induced toxicity, which is augmented by mitochondrion-targeted CYP2E1. We propose that CcO is one of the direct and immediate targets of alcohol-induced toxicity causing respiratory dysfunction.